Penguatan Komunikasi Interpersonal Keluarga Migran di Kota Medan - Abidin, Syahrul (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
Economic needs and demands for welfare are the drivers in migrating abroad as migrant workers which can often cause problems in the family. So it is necessary to build a good communication. Therefore it is important to do a strengthening of interpersonal communication within the family in order to minimize household breakage (broken home). DeVito believes that interpersonal communication is communication that occurs between two people who already have a clear relationship, including family. This writing aims to see the strengthening of the interpersonal communication of migrant families of Indonesian Workers left behind in building harmony in the household. Strengthening is given in the form of verbal reinforcement by showing attitudes, decision responses and agreements in the household between children and parents. The results of this paper indicate that the strengthening of interpersonal communication carried out by migrant families is to increase attention, encourage children's education, lead to divergent ways of thinking or look for their own initiativesÂ